Everything you need to ace biology in one big fat notebook : the complete high school study guide - Brown, Matthew, 1994- (Big fat notebook., 2021)
"The Big Fat Notebooks' big step up to high school continues! Announcing Biology, the third in the high school series. With over 5 million copies in print since 2016, and sales escalating every year, the Big Fat Notebooks series is revolutionizing the middle and high school study guide. And Biology continues with the high school STEM concentration, following Chemistry and Geometry, which in turn followed in the footsteps of the middle school series' bestselling titles, Math (TK million copies in print) and Science (with TK million copies in print). Wrapping its arms around a subject that covers everything from life at the molecular level to the entirety of an ecosystem, Biology tackles all the big ideas: biological classification and hierarchy, cell theory, genetics, the human body, evolution, and more. And it does so in that lively, useful, and intuitive way that makes the Big Fat Notebooks so singular and successful: Critical ideas are broken down and clearly explained; doodles illuminate tricky concepts; mnemonics provide memorable shortcuts; and quizzes recap it all. Plus, the author, Matthew Brown, a biomedical engineer and science communicator, has an easy, engaging way of bringing even the most complex scientific concepts to life"--